The effect of client-centered group play therapy on the level of depression of primary school children: a clinical trial study - Rafati, Fozieh; Daneshi, Fereshte; Rahmati, Reza; Bagheri, Elnazpour (International Journal of Psychosocial Rehabilitation, 2020)
Since the last decade, concurrent with the increasing prevalence of depression among children, special attention has been paid to methods for its prevention and treatment. This study was performed with the aim of examining the impact of client-centered play therapy on the depression of primary school children. The present clinical trial study was conducted 64 primary school students. The participants selected using multistage random sampling method, students with their depression test scores (from CDI questionnaire) greater than 12 were chosen, where 32 (both M/F) were assigned into the control while another 32 (both M/F) were assigned in the test group. The play therapy protocol was 10 sessions each session lasting 45 minutes. One week after the intervention, both groups completed the children depression inventory (CDI) questionnaire. The results showed that there was a significant difference between the mean scores (standard deviation) of posttest between the test and control groups. The posttest scores of the control group were as follows: interpersonal problems 1.91(1.33), no sense of pleasure or anhedonia 5.03(1.66), low self-esteem 1.50(0.04), and negative mood 3.75(1.98). These scores for the test group were as follows: interpersonal problems 0.84(0.77), no sense of pleasure 3.81(1.82), low self-esteem 1.03(0.74), and negative mood 2(1.24). In this study, play therapy caused a significant reduction in the depression scores of the test group in comparison to the control group. Play therapy can be used as an effective intervention to help depressed children.